2020
DOI: 10.1038/s41419-020-02960-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of CBP/p300 HAT by A-485 results in suppression of lipogenesis and hepatic gluconeogenesis

Abstract: The histone acetyltransferases CREB-binding protein (CBP) and its paralogue p300 are transcriptional coactivators which are essential for a multitude of signaling pathways and energy homeostasis. However, the role of CBP/p300 HAT domain in regulating energy balance is still unclear. Here, C57BL/6 mice fed with either normal chow diet (NCD) or high-fat diet (HFD) were administrated with A-485, a recently reported selective inhibitor of CBP/p300 HAT activity for 1 week and the metabolic change was analyzed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 48 publications
3
20
0
Order By: Relevance
“…Moreover, in HFD-fed mice, depletion of liver P300 by shRNA significantly decreased liver glucose production, and the inhibition of P300 acetyltransferase by C646 or A-485 [ 62 , 63 , 64 , 65 ] significantly reduced glucose production in primary hepatocytes and the mRNA levels of G6pc [ 59 , 66 ]. Since the acetylation of CRTC2 by nuclear P300 reduces CRTC2 degradation [ 46 ], elevated P300 protein levels could augment gluconeogenic gene expression by increasing CRTC2 protein levels in HFD-fed mice ( Figure 1 B).…”
Section: Lps-induced Acetyltransferase P300 Upregulates Liver Glucmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in HFD-fed mice, depletion of liver P300 by shRNA significantly decreased liver glucose production, and the inhibition of P300 acetyltransferase by C646 or A-485 [ 62 , 63 , 64 , 65 ] significantly reduced glucose production in primary hepatocytes and the mRNA levels of G6pc [ 59 , 66 ]. Since the acetylation of CRTC2 by nuclear P300 reduces CRTC2 degradation [ 46 ], elevated P300 protein levels could augment gluconeogenic gene expression by increasing CRTC2 protein levels in HFD-fed mice ( Figure 1 B).…”
Section: Lps-induced Acetyltransferase P300 Upregulates Liver Glucmentioning
confidence: 99%
“…Curcumin, an inhibitor for both P300 and CBP acetyltransferase activity, has been used to alleviate hyperglycemia in diabetic patients and animal models [ 121 , 122 , 123 ]. A-485, a more potent and specific inhibitor of both P300 and CBP acetyltransferase activity, alleviated fasting blood glucose levels in HFD-fed mice [ 66 ]. C646, a P300 acetyltransferase-specific inhibitor, significantly improved hyperglycemia and improved insulin sensitivity in obese mice [ 59 ].…”
Section: Perspectivementioning
confidence: 99%
“…In functional studies, p300 overexpression in mice was reported to cause hepatic steatosis, insulin resistance, and inflammation (27). Inhibiting CBP/p300 in mouse liver decreased hepatic lipid content and the expression of lipogenic genes in vivo and also reduced the expression of gluconeogenic genes in primary mouse hepatocytes (130). While this study reported no difference in in vivo insulin sensitivity, mice had reduced fasting glucose and lower glucose levels after glucose loading (130).…”
Section: Histone Acetyltransferases (Hats)mentioning
confidence: 66%
“…Inhibiting CBP/p300 in mouse liver decreased hepatic lipid content and the expression of lipogenic genes in vivo and also reduced the expression of gluconeogenic genes in primary mouse hepatocytes (130). While this study reported no difference in in vivo insulin sensitivity, mice had reduced fasting glucose and lower glucose levels after glucose loading (130). Similarly, CREB activity is positively associated with hepatic IR and NAFLD in mice (131) and its knockdown in mouse liver decreased hepatic and circulating lipid levels and improved insulin sensitivity (132).…”
Section: Histone Acetyltransferases (Hats)mentioning
confidence: 98%
“…It competed with acetyl-CoA for the active site of p300, and selectively inhibited the proliferation of haematological and solid cancer cell lines, such as castration-resistant androgen receptor-positive prostate cancer [22,23]. In addition, A-485 also showed a certain positive effect on liver damage and metabolic diseases [24,25]. On the basis of A-485, Zhou et al identified a preclinical candidate B026 (5) with excellent pharmacological properties with the assistance of artificial intelligence and further optimization [26].…”
Section: Introductionmentioning
confidence: 99%